Predictors of Muscularity Oriented Disordered Eating Behaviors in U.S. Young Adults: A Prospective Cohort Study - Nagata, Jason M. (Int J Eat Disord, 2019)
OBJECTIVE: To determine adolescent predictors of muscularity-oriented disordered eating behaviors in young men and women using a nationally representative longitudinal sample in the US, and to examine differences by sex. METHODS: We used nationally representative longitudinal cohort data collected from baseline (11–18 years old, 1994–1995) and seven-year follow-up (18–24 years old, 2001–2002) of the National Longitudinal Study of Adolescent to Adult Health (Add Health). We examined adolescent demographic, behavioral, and mental health predictors of young adult muscularity-oriented disordered eating behaviors defined as eating more or differently to gain weight or bulk up, supplements to gain weight or bulk up, or androgenic anabolic steroid use at seven-year follow-up. RESULTS: Of the 14,891 included participants, 22% of males and 5% of females reported any muscularity-oriented disordered eating behavior at follow-up in young adulthood. Factors recorded at adolescence that were prospectively associated with higher odds of muscularity-oriented disordered eating in both sexes included Black race, exercising to gain weight, self perception of being underweight, and lower body mass index z-score. In addition, participation in weightlifting; roller-blading, roller-skating, skate-boarding, or bicycling; and alcohol among males and depressive symptoms among females during adolescence were associated with higher odds of muscularity-oriented disordered eating in young adulthood. CONCLUSIONS: Interventions to prevent muscularity-oriented disordered eating behaviors may target at-risk youth, particularly those of Black race or who engage in exercise to gain weight. Future research should examine longitudinal health outcomes associated with muscularity-oriented disordered eating behaviors.